EKSPERIMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DAN TIPE THINK-PAIR-SHARE DENGAN PENDEKATAN SAINTIFIK PADA MATERI POKOK SISTEM PERSAMAAN DAN PERTIDAKSAMAAN LINEAR DITINJAU DARI MOTIVASI BERPRESTASI SISWA - Hartono, Edy; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from studentâs Learning Achievement Motivation. The learning models compared were Problem Based Learning model with scientific approach (PBL-S), Think Pair Share with scientific approach (TPS-S) and classical with scientific approach (Classical -S). The type of the research was a quasi experimental research with the factorial design of 3 x 3. The population were all ten grade students of Senior High School in Madiun City on academic year 2014/2015. The sample consisted of students of SMAN 1 Madiun, SMAN 5 Madiun, and SMAN 4 Madiun, which taken by using stratified cluster random sampling technique. The data of the research were collected through documentation, questionnaire, and test. The data was analyzed using unbalanced two-ways anova at the significance level of 0.05. Based on the data analysis, it can be concluded as follows. (1) PBL-S gives better mathematics achievement than TPS-S and Classical-S, whereas TPS-S gives better mathematics learning achievement than Classical-S. (2) Students with high Learning Achievement Motivation are better in mathematics learning achievement than students with medium and low Learning Achievement Motivation, and also medium Learning Achievement Motivation have better mathematics learning achievement than low Learning Achievement Motivation. (3) For PBL-S, students with high Learning Achievement Motivation give better mathematics learning achievement than medium and low Learning Achievement Motivation, whereas students with medium and low Learning Achievement Motivation have the same mathematics learning achievement. For TPS-S with medium Learning Achievement Motivation gives the same mathematics learning achievement with high and low Learning Achievement Motivation, also high Learning Achievement Motivation gives better mathematics learning achievement than low Learning Achievement Motivation. For Classical-S, students with high, medium, and low Learning Achievement Motivation give the same mathematics learning achievement. (4) For students with high Learning Achievement Motivation, TPS-S gives the same mathematics learning achievement with PBL-S and Classical-S, whereas PBL-S gives better mathematics learning achievement than Classical-S. For students with medium and low Learning Achievement Motivation, all learning models give the same mathematics achievement.Keywords: PBL, TPS, scientific approach, classical learning, learning achievement motivation, learning achievementÂ